VD_FINDINFO Plainte / 2015 / 35 vom 18. Oktober 2015 - VD Tribunal cantonal (2015)
PLAINTELP, CESSION DES DROITS DE LA MASSE, NULLITÉ, RÉVOCATIONEN GÉNÉRAL, PLAINTE PÉNALE, RESTITUTION DU DÉLAI, DROIT D'ÊTRE ENTENDU | 29 al. 2 Cst., 17 al. 1 LP, 17 al. 2 LP, 22 al. 1 LP, 260 LP, 33 al. 4 LP